Data literacy for citizenry: A few policy recommendations from a literature review - Salomao Filho, Alfredo; Wasson, Barbara; Lameras, Petros; Maloszek, Ruth (Edutec, 2023)
There has been a massive increase in digitalization and datafication within societies over the last years. In this context, the concept of data literacy has also gained in importance, as it is seen as one of the skills that citizens require in order to navigate and participate in society. However, despite the relevance of the concept, it is yet to be discussedas to the ways to promote it at the institutional level. In order to perform such a task, we conducted a review that combines approaches from a mapping review with that of a traditional narrative review, making a series of policy recommendations towards a data literate society. Focusing on the period between 2015 and 2021, we analysed a corpus of 39 empirical and theoretical studies. Findings confirm the scattered and interdisciplinary nature of research on data literacy, yet paving the way for a series of recommendations to promote the former.<br
Keywords: data literacy; citizenry; adult education; policy recommendations; systematic review